2024
DOI: 10.1007/s00262-024-03644-2
|View full text |Cite|
|
Sign up to set email alerts
|

The radiomics nomogram predicts the prognosis of pancreatic cancer patients with hepatic metastasis after chemoimmunotherapy

Wenxin Lu,
Guangyu Wu,
Xianyuan Miao
et al.

Abstract: Objective To construct a prognostic model based on MR features and clinical data to evaluate the progression free survival (PFS), overall survival (OS) and objective response rate (ORR) of pancreatic cancer patients with hepatic metastases who received chemoimmunotherapy. Methods 105 pancreatic cancer patients with hepatic metastases who received chemoimmunotherapy were assigned to the training set (n = 52), validation set (n = 22), and testing set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…2 A recent study demonstrated that prognostic radiomics models, incorporating MRI features and clinical data, are effective in predicting progression-free survival, overall survival, and objective response rate in PC patients with hepatic metastasis undergoing chemoimmunotherapy. 17 These models hold promise for evaluating patient prognosis.…”
mentioning
confidence: 99%
“…2 A recent study demonstrated that prognostic radiomics models, incorporating MRI features and clinical data, are effective in predicting progression-free survival, overall survival, and objective response rate in PC patients with hepatic metastasis undergoing chemoimmunotherapy. 17 These models hold promise for evaluating patient prognosis.…”
mentioning
confidence: 99%